Stability of bocaiuva (Acrocomia spp.) mass candy stored in different packages - THEODORO, Ângela Christina Conte; DONADON, Juliana Rodrigues; GUASQUES, Maria Luiza Brambilla; MIYAGUSKU, Luciana; POTT, Arnildo; GALVANI, Fábio; GUIMARÃES, Rita de Cássia Avellaneda; BOGO, Danielle; NASCIMENTO, Valter Aragão do; HIANE, Priscila Aiko (Food Science and Technology, 2024)
Bocaiuva (Acrocomia spp.) is a fruit native to areas of Cerrado and Pantanal that stands out for its nutritional value, presence of bioactive substances, and high pulp yield. The aim of this study was to develop a mass candy of bocaiuva, characterize it physicochemically, quantify the retention of bioactive substances, evaluate the physicochemical and microbiological stability and sensorial acceptance for up to 120 days, and verify the effect of different types of packages and storage time on the developed product quality. The prepared mass candy was stored in plastic packages of terephthalate polyethene that were transparent and metallized. We have characterized its centesimal composition and microbiological and sensorial stability, evaluating its color, moisture, pH, soluble solids, titrable acidity, retention of ascorbic acid, carotenoids, total phenolics, and antioxidant capacity. The results indicated that the bocaiuva mass candy stays stable for physicochemical, microbiological, and sensory parameters over storage and that the metallized polyethene terephthalate package best conserves the bioactive substances.